Composition for electrochemical device, positive electrode mixture, positive electrode structure and secondary battery
By using a composition for electrochemical devices containing a single layer of carbon nanotubes and a fluorine-containing copolymer, the problems of high resistance and rebound of the electrode mixture layer are solved, and the low resistance, high adhesion and softness of the battery are achieved.
Patent Information
- Application Number
- CN202080046988.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-01
- Filing Date
- 2020-06-30
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-06-30
AI Technical Summary
The conventional electrochemical device compositions tend to increase viscosity after preparation, resulting in high resistance of the electrode mixture layer and it is difficult to form an electrode mixture layer with excellent adhesion and flexibility with the current collector.
The electrochemical device composition containing a single layer of carbon nanotubes, fluorine-containing copolymers and solvents, wherein the binder of the fluorine-containing copolymer contains vinylidene fluoride units and fluorinated monomer units, and is optimized by dynamic viscoelastic determination. Energy storage modulus of the composition.
The low resistance, high adhesion and flexibility of the electrode mixture layer are achieved, and the problem of the electrode mixture layer rebounding after heat treatment is avoided, and the output characteristics and circulation characteristics of the battery are improved.
Smart Images

Figure BDA0003435243100000071 
Figure BDA0003435243100000141 
Figure BDA0003435243100000341
Abstract
Description
Technical Field
[0001] The present invention relates to a composition for an electrochemical device, a positive electrode mixture, a positive electrode structure and a secondary battery. Background Art
[0002] Secondary batteries such as lithium-ion secondary batteries are used in small and portable electrical and electronic devices such as notebook personal computers, mobile phones, smart phones, tablet computers, and ultra-notebooks due to their high voltage, high energy density, low self-discharge, low memory effect, and ability to be ultra-lightweight. They are also being put into practical use as power sources such as on-board power sources for driving automobiles and large power sources for stationary use.
[0003] For example, Patent Document 1 describes a secondary battery having a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a first negative electrode active material, a second negative electrode active material and a negative electrode binder, wherein the first negative electrode active material comprises a central portion and a covering portion, wherein the central portion comprises a material comprising silicon (Si) as a constituent element, wherein the covering portion is provided on the surface of the central portion and comprises a salt compound and a conductive material, wherein the salt compound comprises at least one of a polyacrylic acid salt and a carboxymethyl cellulose salt, wherein the conductive material comprises at least one of a carbon material and a metal material, wherein the second negative electrode active material comprises a material comprising carbon (C) as a constituent element, and wherein the negative electrode binder comprises at least one of polyvinylidene fluoride, polyimide and aromatic polyamide. In addition, Patent Document 1 exemplifies single-walled carbon nanotubes as carbon materials.
[0004] Patent Document 2 describes a metal foil having a surface provided with a conductive layer containing carbon nanotubes, wherein the conductive layer contains carbon nanotubes at a concentration of 100 ng / cm 2 ~10 μg / cm 2 A conductive layer is applied in a manner that the carbon nanotubes are randomly configured.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2018 / 146865
[0008] Patent Document 2: European Patent Application Publication No. 3147919 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The purpose of the present invention is to provide a composition for an electrochemical device, which can obtain an electrode mixture whose viscosity is not easy to increase even after a long time after preparation, and further, can form an electrode mixture layer with low resistance, and at the same time can form an electrode mixture layer with excellent adhesion and softness to the collector and is not easy to rebound.
[0011] Means for solving problems
[0012] According to the present invention, a composition for an electrochemical device is provided, which is a composition for an electrochemical device containing single-layer carbon nanotubes, a binder and a solvent, wherein the binder contains a fluorinated copolymer comprising vinylidene fluoride units and fluorinated monomer units (which do not include vinylidene fluoride units), and the content of the vinylidene fluoride units in the fluorinated copolymer is greater than 50.0 mol% relative to all monomer units.
[0013] The average outer diameter of the single-walled carbon nanotubes is preferably 2.5 nm or less.
[0014] The average G / D ratio of the single-walled carbon nanotubes is preferably 2 or more.
[0015] The content of the fluorinated monomer units in the fluorinated copolymer is preferably at least 1.0 mol % based on all monomer units.
[0016] The fluorinated monomer unit is preferably at least one selected from the group consisting of a tetrafluoroethylene unit, a chlorotrifluoroethylene unit, a fluoroalkyl vinyl ether unit, and a hexafluoropropylene unit.
[0017] The fluorinated monomer unit is more preferably at least one selected from the group consisting of tetrafluoroethylene units and hexafluoropropylene units.
[0018] The fluorinated copolymer preferably has a storage modulus (E') at 30°C obtained by dynamic viscoelasticity measurement of 100 to 1200 MPa, and preferably has a storage modulus (E') at 60°C of 50 to 600 MPa.
[0019] The above-mentioned binder preferably further contains polyvinylidene fluoride.
[0020] The solvent is preferably at least one selected from the group consisting of N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone and β-alkoxypropionamides.
[0021] The composition for an electrochemical device of the present invention is suitably used to form an electrode or a separator of an electrochemical device.
[0022] Furthermore, according to the present invention, there is provided a positive electrode mixture comprising the above-mentioned composition for an electrochemical device and a positive electrode active material.
[0023] The content of the single-walled carbon nanotubes in the positive electrode mixture is preferably 0.001 parts by mass to 10 parts by mass based on 100 parts by mass of the positive electrode active material.
[0024] The content of the binder in the positive electrode mixture is preferably 0.1 parts by mass to 5.0 parts by mass based on 100 parts by mass of the positive electrode active material.
[0025] According to the present invention, there is provided a positive electrode structure including a current collector and a positive electrode mixture layer formed of the positive electrode mixture and provided on one or both surfaces of the current collector.
[0026] Furthermore, according to the present invention, there is provided a secondary battery including the above-mentioned positive electrode structure.
[0027] Effects of the Invention
[0028] According to the present invention, a composition for an electrochemical device can be provided, which can obtain an electrode mixture whose viscosity is not easy to increase even after a long time after preparation, and further, can form an electrode mixture layer with low resistance, and can also form an electrode mixture layer that has excellent adhesion and softness to the collector and is not easy to rebound. DETAILED DESCRIPTION
[0029] Hereinafter, specific embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.
[0030] Composition for electrochemical device
[0031] The composition for an electrochemical device of the present invention contains single-walled carbon nanotubes, a binder and a solvent.
[0032] Single-walled carbon nanotube
[0033] The composition for electrochemical devices of the present invention contains single-layer carbon nanotubes. Single-layer carbon nanotubes (SWCNTs) are a special type of carbon material known as a one-dimensional material. Single-layer carbon nanotubes are composed of sheets of graphene, which are wound to form a hollow tube with a wall of 1 atom thickness. By having such a chemical structure and size, single-layer carbon nanotubes show excellent mechanical, electrical, thermal and optical properties. Since the composition for electrochemical devices of the present invention contains single-layer carbon nanotubes, an electrode mixture is prepared using the composition for electrochemical devices of the present invention, and an electrode mixture layer is formed using the obtained electrode mixture, thereby forming an electrode mixture layer with low resistance. Therefore, when forming an electrode mixture layer with the same resistance as an existing electrode mixture layer, the total amount of conductive additives such as acetylene black can be reduced, and the amount of active substances can be increased, thereby realizing an electrochemical device with high energy density. In addition, by using single-layer carbon nanotubes together with a specific copolymer described later, the adhesion of the electrode mixture layer to the collector and the flexibility of the electrode structure with the electrode mixture layer and the collector can be taken into account.
[0034] Moreover, the electrode mixture layer obtained by using the composition for electrochemical devices of the present invention also has the effect of being difficult to rebound. When forming an electrode with an electrochemical device, in order to make the electrode thinner and flatter, or to increase the electrode density, a pressing process is performed, and a heat treatment is performed after the pressing process. In the prior art, when the pressing load generated by the pressing process is released and the heat treatment is performed, there is a problem of an increase in the thickness of the electrode or a decrease in the electrode density (rebound). By using a single-layer carbon nanotube together with a specific copolymer described later, the rebound can be effectively suppressed.
[0035] Furthermore, by using the composition for an electrochemical device of the present invention, a battery having excellent output characteristics, cycle characteristics, and 60° C. storage characteristics can be obtained.
[0036] The average outer diameter of the single-walled carbon nanotube is preferably 1.0 nm to 2.5 nm, more preferably 1.1 nm to 2.0 nm, and further preferably 1.2 nm to 1.8 nm. The average outer diameter of the single-walled carbon nanotube can be obtained from the light absorption spectrum of the single-walled carbon nanotube obtained by ultraviolet visible near infrared spectroscopy (UV-Vis-NIR), Raman spectrum or transmission electron microscope (TEM) image.
[0037] The average length of the single-walled carbon nanotubes is preferably 0.1 μm to 50 μm, more preferably 0.5 μm to 20 μm, and further preferably 1 μm to 10 μm. The average length of the single-walled carbon nanotubes can be obtained by obtaining an AFM image of the single-walled carbon nanotubes using an atomic force microscope (AFM), or obtaining a TEM image of the single-walled carbon nanotubes using a transmission electron microscope (TEM), measuring the length of each single-walled carbon nanotube, and dividing the total value of the length by the number of the single-walled carbon nanotubes measured.
[0038] The average G / D ratio of the single-walled carbon nanotube measured by Raman spectroscopy (wavelength 532nm) is preferably 2 to 250, more preferably 5 to 250, further preferably 10 to 220, and particularly preferably 40 to 180. The G / D ratio refers to the intensity ratio (G / D) of the G band and the D band of the Raman spectrum of the single-walled carbon nanotube. The higher the average G / D ratio of the single-walled carbon nanotube, the higher the crystallinity of the single-walled carbon nanotube, and the fewer impurity carbon and defective carbon nanotubes.
[0039] The content of the single-layer carbon nanotubes in the composition for electrochemical devices of the present invention is preferably 0.01% to 3% by mass, more preferably 0.01% to 2% by mass, further preferably 0.01% to 1% by mass, particularly preferably 0.1% to 0.8% by mass, and most preferably 0.2% to 0.5% by mass, relative to the mass of the composition. When the content of the single-layer carbon nanotubes is within the above range, the composition for electrochemical devices has a moderate viscosity, and an electrode mixture in which each component is fully dispersed can be prepared without applying excessive shear force. Therefore, in the obtained electrode mixture layer, a three-dimensional network of single-layer carbon nanotubes is fully formed, and an electrode mixture layer with lower resistance can be obtained.
[0040] Binder
[0041] The composition for electrochemical devices of the present invention contains a fluorinated copolymer containing a vinylidene fluoride unit and a fluorinated monomer unit (which does not include a vinylidene fluoride unit) as a binder. Since the composition for electrochemical devices of the present invention contains the above-mentioned fluorinated copolymer, it is possible to prepare an electrode mixture whose viscosity is not easy to increase even after a long time after preparation. In particular, even when the composition for electrochemical devices of the present invention is mixed with a positive electrode active material having a large Ni content, the viscosity of the obtained positive electrode mixture is difficult to increase. In addition, since the composition for electrochemical devices of the present invention contains the above-mentioned fluorinated copolymer together with the above-mentioned single-layer carbon nanotubes, by using the composition for electrochemical devices of the present invention to prepare an electrode mixture, and using the obtained electrode mixture to form an electrode mixture layer, it is possible to take into account the adhesion of the electrode mixture layer to the collector and the flexibility of the electrode structure, and can effectively suppress the rebound of the electrode mixture layer.
[0042] As the fluorine-containing copolymer, a fluorine resin is preferably used. The fluorine resin refers to a partially crystalline fluorine-containing polymer, which is not a fluorine rubber but a fluorine plastic. The fluorine resin has a melting point and is thermoplastic, and can be melt-processable or non-melt-processable. As the fluorine resin, a melt-processable fluorine resin is preferably used.
[0043] As the fluorinated monomer (excluding VdF), from the perspective of forming an electrode mixture layer that can further suppress the increase in viscosity of the electrode mixture, has better adhesion and flexibility to the collector, and is less likely to rebound, it is preferably selected from at least one of the group consisting of tetrafluoroethylene (TFE), vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), fluoroalkyl vinyl ether, hexafluoropropylene (HFP), (perfluoroalkyl)ethylene, 2,3,3,3-tetrafluoropropylene and trans-1,3,3,3-tetrafluoropropylene, more preferably selected from at least one of the group consisting of TFE, CTFE, fluoroalkyl vinyl ether and HFP, further preferably selected from at least one of the group consisting of TFE, fluoroalkyl vinyl ether and HFP, and particularly preferably selected from at least one of the group consisting of TFE and HFP. From the perspective of being able to suppress the swelling of the electrode mixture layer to the electrolyte, and improving battery characteristics such as output characteristics, cycle characteristics, and low resistance, TFE is most preferred.
[0044] The fluorinated monomer units (excluding the VdF unit) may or may not have a polar group.
[0045] Examples of the fluoroalkyl vinyl ether (FAVE) include those selected from the group consisting of
[0046] General formula: CF2 = CFO (CF2CFX 1 O) p -(CF2CF2CF2O) q -Rf 1
[0047] (Where X 1 Indicates F or CF3, Rf 1 represents a perfluoroalkyl group having 1 to 5 carbon atoms. p represents an integer of 0 to 5, and q represents an integer of 0 to 5) and
[0048] General formula: CFX 2 =CX 2 OCF2O 2
[0049] (Where X 2 Same or different, represents H, F or CF3, Rf 2 It represents at least one of the monomers represented by a linear or branched fluoroalkyl group having 1 to 6 carbon atoms which may or may not contain 1 to 2 at least one atom selected from the group consisting of H, Cl, Br and I, or a cyclic fluoroalkyl group having 5 or 6 carbon atoms which may or may not contain 1 to 2 at least one atom selected from the group consisting of H, Cl, Br and I.
[0050] As FAVE, at least one selected from the group consisting of perfluoro(methyl vinyl ether) (PMVE), perfluoro(ethyl vinyl ether) (PEVE) and perfluoro(propyl vinyl ether) (PPVE) is more preferred.
[0051] The content of the VdF unit of the fluorinated copolymer is 50.0 mol% or more relative to the total monomer units. From the perspective of being able to form an electrode mixture layer that can further suppress the increase in viscosity of the electrode mixture, has lower resistance, better adhesion and flexibility to the collector, and is less likely to rebound, it is preferably 55.0 mol% or more, more preferably 60.0 mol% or more, preferably 99.0 mol% or less, more preferably 97.0 mol% or less, further preferably 95.0 mol% or less, and particularly preferably 90.0 mol% or less.
[0052] From the perspective of being able to form an electrode mixture layer that can further suppress the increase in viscosity of the electrode mixture, has lower resistance, better adhesion and flexibility to the collector, and is less likely to rebound, the content of fluorinated monomer units (excluding VdF units) of the fluorinated copolymer is preferably 1.0 mol% or more, more preferably 2.5 mol% or more, further preferably 5.0 mol% or more, particularly preferably 8.0 mol% or more, most preferably 10.0 mol% or more, preferably 50.0 mol% or less, more preferably 49.5 mol% or less, further preferably 45.0 mol% or less, and particularly preferably 40.0 mol% or less.
[0053] In this specification, the composition of the fluorinated copolymer can be, for example, 19 The results were determined by F-NMR measurement.
[0054] The fluorinated copolymer may further contain a non-fluorinated monomer unit. Examples of the non-fluorinated monomer include non-fluorinated monomers having no polar group such as ethylene and propylene, and non-fluorinated monomers having a polar group (hereinafter sometimes referred to as a polar group-containing monomer).
[0055] If a substance with a polar group is used as a non-fluorinated monomer, the polar group is introduced into the fluorinated copolymer, so that the electrode mixture layer and the collector can be more excellently adhered. As the polar group that the fluorinated copolymer can have, it is preferably selected from at least one of the groups consisting of a carbonyl-containing group, an epoxy group, a hydroxyl group, a sulfonic acid group, a sulfuric acid group, a phosphoric acid group, an amino group, an amide group and an alkoxy group, more preferably selected from at least one of the groups consisting of a carbonyl-containing group, an epoxy group and a hydroxyl group, and further preferably a carbonyl-containing group. The above-mentioned hydroxyl group does not include a hydroxyl group constituting a part of the above-mentioned carbonyl-containing group. In addition, the above-mentioned amino group refers to a univalent functional group obtained after removing hydrogen from ammonia, a primary amine or a secondary amine.
[0056] The above-mentioned carbonyl-containing group refers to a functional group having a carbonyl group (-C(=O)-). As the above-mentioned carbonyl-containing group, from the perspective of obtaining a better adhesion between the electrode mixture layer and the collector, a group represented by the general formula: -COOR (R represents a hydrogen atom, an alkyl group or a hydroxyalkyl group) or a carboxylic anhydride group is preferred, and a group represented by the general formula: -COOR is more preferred. The number of carbon atoms of the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and further preferably 1 to 3. As the group represented by the general formula: -COOR, specifically, -COOCH2CH2OH, -COOCH2CH(CH3)OH, -COOCH(CH3)CH2OH, -COOH, -COOCH3, -COOC2H5, etc. can be cited. When the group represented by the general formula: -COOR is -COOH, or contains -COOH, -COOH can be a carboxylate group such as a metal carboxylate group or an ammonium carboxylate group.
[0057] As the above-mentioned amide group, preferably, a group represented by the general formula: -CO-NRR' (R and R' independently represent a hydrogen atom or a substituted or unsubstituted alkyl group), or a bond represented by the general formula: -CO-NR"- (R" represents a hydrogen atom, a substituted or unsubstituted alkyl group or a substituted or unsubstituted phenyl group).
[0058] Examples of the above-mentioned polar group-containing monomer include: (meth) hydroxyalkyl acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; alkylidene malonates such as dimethyl methylene malonate; vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether; (meth) carboxyalkyl acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate; (meth) acryloxyalkyl dicarboxylates such as acryloxyethyl succinate, methacryloxyethyl succinate, acryloxyethyl phthalate, and methacryloxyethyl phthalate; and monoesters of unsaturated dibasic acids such as monomethyl maleate, monoethyl maleate, monomethyl citraconic acid, and monoethyl citraconic acid; General formula (2):
[0059] [Chemistry 1]
[0060]
[0061] (Where R 1 ~R 3 R independently represents a hydrogen atom, a chlorine atom or a hydrocarbon group having 1 to 8 carbon atoms. 4 represents a single bond, a hydrocarbon group having 1 to 8 carbon atoms, a heteroatom, or an atomic group having a molecular weight of 500 or less and containing at least one heteroatom selected from the group consisting of an oxygen atom, a sulfur atom, a nitrogen atom, and a phosphorus atom and having a main chain having 1 to 20 atoms. 1represents an inorganic cation and / or an organic cation); etc. It should be noted that, in the present invention, "(meth)acrylic acid" refers to any one of acrylic acid and methacrylic acid. The "(meth)" in other compound names shall be interpreted in the same way. In addition, the number of atoms in the main chain of the atomic group is the number of atoms in the straight chain skeleton portion, and the oxygen atoms constituting the carbonyl group and the hydrogen atoms constituting the methylene group are not included in the number of atoms in the main chain. For example, when monomer (2) is acryloyloxyethyl phthalate, the straight chain skeleton portion is -C-OCCO-C-CC-, and its atomic number is 8.
[0062] The fluorinated copolymer preferably contains a unit based on a monomer (2) represented by the general formula (2) as the polar group-containing monomer, since it can form an electrode mixture layer which is more excellent in adhesion to the current collector and flexibility and less likely to rebound.
[0063] In the general formula (2), Y 1 represents an inorganic cation and / or an organic cation. Examples of inorganic cations include cations such as H, Li, Na, K, Mg, Ca, Al, and Fe. Examples of organic cations include NH4, NH3R 5 NH2R 5 2. NHR 5 3. NR 5 4(R 5 and Y independently represents a cation such as an alkyl group having 1 to 4 carbon atoms. 1 , preferably H, Li, Na, K, Mg, Ca, Al, NH4, more preferably H, Li, Na, K, Mg, Al, NH4, further preferably H, Li, Al, NH4, and particularly preferably H. It should be noted that, for the sake of convenience, specific examples of inorganic cations and organic cations are recorded with symbols and valences omitted.
[0064] In the general formula (2), R 1 ~R 3 R independently represents a hydrogen atom, a chlorine atom or a hydrocarbon group having 1 to 8 carbon atoms. The hydrocarbon group is a monovalent hydrocarbon group. The number of carbon atoms of the hydrocarbon group is preferably 4 or less. Examples of the hydrocarbon group include alkyl, alkenyl, alkynyl, etc. having the above-mentioned carbon number, preferably methyl or ethyl. 1 and R 2 R 3 Preferred is a hydrogen atom or a methyl group.
[0065] In the general formula (2), R 4It represents a single bond, a hydrocarbon group having 1 to 8 carbon atoms, a heteroatom, or an atomic group having a molecular weight of 500 or less and having a main chain having 1 to 20 atoms and containing at least one heteroatom selected from the group consisting of an oxygen atom, a sulfur atom, a nitrogen atom, and a phosphorus atom.
[0066] The hydrocarbon group is a divalent hydrocarbon group. The number of carbon atoms in the hydrocarbon group is preferably 4 or less. Examples of the hydrocarbon group include alkylene groups and alkenylene groups having the above-mentioned number of carbon atoms, among which at least one selected from the group consisting of methylene, ethylene, ethylidene, propylidene and isopropylidene is preferred, and at least one selected from the group consisting of methylene and ethylene is more preferred.
[0067] R 4 In the case of a hetero atom, the hetero atom is preferably at least one selected from the group consisting of an oxygen atom, a sulfur atom, a nitrogen atom and a phosphorus atom, and more preferably an oxygen atom.
[0068] R 4 In the case of an atomic group, an oxygen atom is preferably used as the heteroatom in the atomic group.
[0069] R 4 When it is an atomic group, the general formula in the general formula (2): -R 4 -CO2Y 1 The side chain shown is preferably any of the following.
[0070] General formula: -CO-R 6 -CO2Y 1 The side chains shown
[0071] (Where R 6 It represents an atomic group having a main chain with 1 to 19 atoms and a molecular weight of 472 or less. 1 As described above.)
[0072] General formula: -OR 7 -CO2Y 1 The side chains shown
[0073] (Where R 7 It represents an atomic group having a molecular weight of 484 or less and including a main chain having 1 to 19 atoms. 1 As described above.)
[0074] General formula: -COO-R 8 -CO2Y 1 The side chains shown
[0075] (R 8 It is an atomic group having a molecular weight of 456 or less and including a main chain having 1 to 18 atoms. 1 As described above.)
[0076] R 4 When it is an atomic group, examples of monomer (2) include (meth)acrylamide compounds such as N-carboxyethyl (meth)acrylamide; thio (meth)acrylate compounds such as carboxyethylthio (meth)acrylate; vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether; 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, succinic acid acryloxyethyl ester, succinic acid methacrylic acid methyl ester, succinic acid acryloxypropyl ester, succinic acid methyl ester, phthalic acid acryloxyethyl ester, phthalic acid methyl ester; etc. R 4 In the case of an atomic group, the monomer (2) is preferably 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, acryloyloxyethyl succinate, methacryloyloxyethyl succinate, acryloyloxypropyl succinate, or methacryloyloxypropyl succinate.
[0077] As the monomer (2), R in the general formula (2) is preferably 4 A monomer (2) which is a single bond or a hydrocarbon group having 1 to 8 carbon atoms.
[0078] As monomer (2), from the perspective of being able to form an electrode mixture layer that has better adhesion and flexibility to the collector and is less likely to rebound, it is more preferred to select at least one of the group consisting of (methyl) acrylic acid and its salts, vinylacetic acid (3-butenoic acid) and its salts, 3-pentenoic acid and its salts, 4-pentenoic acid and its salts, 3-hexenoic acid and its salts, 4-heptenoic acid and its salts, and 5-hexenoic acid and its salts, and it is further preferred to select at least one of the group consisting of 3-butenoic acid and its salts and 4-pentenoic acid and its salts.
[0079] From the perspective of being able to form an electrode mixture layer that can further suppress the increase in viscosity of the electrode mixture, has lower resistance, better adhesion and flexibility to the collector, and is less likely to rebound, the content of the above-mentioned polar group-containing monomer units in the fluorinated copolymer is preferably 0.05 mol% to 2.0 mol% relative to all monomer units, more preferably 0.10 mol% or more, further preferably 0.25 mol% or more, particularly preferably 0.40 mol% or more, and more preferably 1.5 mol% or less.
[0080] In the present specification, when the polar group is an acid group such as carboxylic acid, for example, the content of the polar group-containing monomer unit in the fluorinated copolymer can be measured by acid-base titration of the acid group.
[0081] Examples of the fluorine-containing copolymer include VdF / TFE copolymers, VdF / HFP copolymers, VdF / TFE / HFP copolymers, VdF / TFE / (meth)acrylic acid copolymers, VdF / HFP / (meth)acrylic acid copolymers, VdF / CTFE copolymers, VdF / TFE / 4-pentenoic acid copolymers, VdF / TFE / 3-butenoic acid copolymers, VdF / TFE / HFP / (meth)acrylic acid copolymers, VdF / TFE / HFP / 4-pentenoic acid copolymers, VdF / TFE / HFP / 3-butenoic acid copolymers, VdF / FAVE copolymers, VdF / FAVE / (meth)acrylic acid copolymers, VdF / FAVE / carboxyalkyl(meth)acrylate copolymers, and VdF / HFP / carboxyalkyl(meth)acrylate.
[0082] The fluorinated copolymer is preferably at least one selected from the group consisting of a copolymer containing a VdF unit and a TFE unit, a copolymer containing a VdF unit and a HFP unit, and a copolymer containing a VdF unit and a FAVE unit.
[0083] As the fluorinated copolymer, it is preferred that the fluorinated copolymer is composed only of VdF units, TFE units and any non-fluorinated monomer units and the molar ratio of VdF units to TFE units (VdF units / TFE units) is 50 / 50 to 90 / 10. That is, the fluorinated copolymer is preferably a binary copolymer composed only of VdF units and TFE units, or a ternary or higher copolymer composed only of VdF units, TFE units and non-fluorinated monomer units, and does not contain fluorinated monomer units other than VdF units and TFE units. The composition for electrochemical devices of the present invention can form an electrode mixture layer that can further suppress the increase in viscosity of the electrode mixture, has lower resistance, has better adhesion and flexibility to the collector, and is more difficult to rebound by containing the above-mentioned fluorinated copolymer.
[0084] When the fluorinated copolymer contains VdF units and TFE units, the molar ratio of the VdF units to the TFE units (VdF units / TFE units) is preferably from 50 / 50 to 90 / 10, more preferably from 55 / 45 to 89 / 11, further preferably from 60 / 40 to 88 / 12.
[0085] When the fluorinated copolymer contains VdF units and TFE units, the content of the non-fluorinated monomer units is preferably from 0 to 2.0 mol % based on the total monomer units of the fluorinated copolymer.
[0086] As the non-fluorinated monomer, a polar group-containing monomer is preferred, more preferably monomer (2), further preferably at least one selected from the group consisting of (meth)acrylic acid and its salts, vinylacetic acid (3-butenoic acid) and its salts, 3-pentenoic acid and its salts, 4-pentenoic acid and its salts, 3-hexenoic acid and its salts, 4-heptenoic acid and its salts and 5-hexenoic acid and its salts, particularly preferably at least one selected from the group consisting of 3-butenoic acid and its salts and 4-pentenoic acid and its salts.
[0087] As the fluorinated copolymer consisting only of VdF units, TFE units and any non-fluorinated monomer units, it is preferred that at least one selected from the group consisting of VdF / TFE copolymers, VdF / TFE / HFP copolymers, VdF / TFE / (meth)acrylic acid copolymers, VdF / TFE / 4-pentenoic acid copolymers, VdF / TFE / 3-butenoic acid copolymers, VdF / TFE / HFP / (meth)acrylic acid copolymers, VdF / TFE / HFP / 4-pentenoic acid copolymers and VdF / TFE / HFP / 3-butenoic acid copolymers.
[0088] The fluorine-containing copolymer can be a VdF / HFP copolymer. The VdF / HFP copolymer contains a VdF unit and an HFP unit. As the content of the VdF unit, relative to the total monomer units of the VdF / HFP copolymer, it is preferably 55.0 mol% or more, more preferably 60.0 mol% or more, further preferably 80.0 mol% or more, particularly preferably 90.0 mol% or more, preferably 99.0 mol% or less, more preferably 97.0 mol% or less. As the content of the HFP unit, relative to the total monomer units of the VdF / HFP copolymer, it is preferably 1.0 mol% or more, more preferably 3.0 mol% or more, preferably 45.0 mol% or less, more preferably 40.0 mol% or less, further preferably 20.0 mol% or less, particularly preferably 10.0 mol% or less.
[0089] In addition to VdF units and HFP units, the VdF / HFP copolymer may also include units based on monomers copolymerizable with VdF and HFP (excluding VdF and HFP). The content of the units based on monomers copolymerizable with VdF and HFP is preferably 0 to 2.0 mol%, more preferably 0.05 mol% to 2.0 mol% relative to the total monomer units of the VdF / HFP copolymer.
[0090] Examples of the monomer copolymerizable with VdF and HFP include the above-mentioned fluorinated monomers, the above-mentioned non-fluorinated monomers, etc. The monomer copolymerizable with VdF and HFP is preferably at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers, more preferably at least one selected from the group consisting of TFE, 2,3,3,3-tetrafluoropropylene and monomer (2), and still more preferably monomer (2).
[0091] The fluorinated copolymer can be a VdF / FAVE copolymer. The VdF / FAVE copolymer contains a VdF unit and a FAVE unit. As the content of the VdF unit, relative to all monomer units of the VdF / FAVE copolymer, it is preferably 55.0 mol% or more, more preferably 70.0 mol% or more, further preferably 90.0 mol% or more, particularly preferably 95.0 mol% or more, preferably 99.0 mol% or less, more preferably 98.5 mol% or less. As the content of the FAVE unit, relative to all monomer units of the VdF / FAVE copolymer, it is preferably 1.0 mol% or more, more preferably 1.5 mol% or more, preferably 45.0 mol% or less, more preferably 30.0 mol% or less, further preferably 10.0 mol% or less, particularly preferably 5.0 mol% or less.
[0092] As FAVE, at least one selected from the group consisting of perfluoro(methyl vinyl ether) (PMVE), perfluoro(ethyl vinyl ether) (PEVE) and perfluoro(propyl vinyl ether) (PPVE) is preferred.
[0093] In addition to VdF units and FAVE units, VdF / FAVE copolymers may also include units based on monomers copolymerizable with VdF and FAVE (wherein VdF and FAVE are not included). The content of units based on monomers copolymerizable with VdF and FAVE is preferably 0 to 2.0 mol%, more preferably 0.05 mol% to 2.0 mol%, relative to all monomer units of the VdF / FAVE copolymer.
[0094] As the monomers copolymerizable with VdF and FAVE, there can be mentioned the above-mentioned fluorinated monomers, the above-mentioned non-fluorinated monomers, etc. As the monomers copolymerizable with VdF and FAVE, at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers is preferred, a polar group-containing monomer is more preferred, and at least one selected from the group consisting of (meth)acrylic acid and its salts and (meth)acrylic acid carboxyalkyl esters and their salts is further preferred.
[0095] The weight average molecular weight (polystyrene equivalent) of the fluorinated copolymer is preferably from 160000 to 2760000, more preferably from 200000 to 2530000, further preferably from 300000 to 2000000. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0096] The number average molecular weight (polystyrene equivalent) of the fluorinated copolymer is preferably from 70000 to 1200000, more preferably from 140000 to 1100000. The number average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0097] The melting point of the fluorinated copolymer is preferably 100 to 200° C. The melting point can be determined using a differential scanning calorimeter (DSC) apparatus as a temperature relative to a local maximum in a heat of fusion curve when the temperature is increased at a rate of 10° C. / min.
[0098] The average particle size of the fluorinated copolymer is preferably 1000 μm or less, more preferably 50 μm to 350 μm, from the viewpoint of being able to easily dissolve or disperse the fluorinated copolymer in a solvent.
[0099] The fluorinated copolymer preferably has a storage modulus (E') at 30°C of 100 to 1200 MPa and a storage modulus (E') at 60°C of 50 to 600 MPa.
[0100] The storage modulus (E') of the fluorinated copolymer at 30°C is more preferably at least 150 MPa, further preferably at least 200 MPa, and is more preferably at most 800 MPa, further preferably at most 600 MPa.
[0101] The storage modulus (E') of the fluorinated copolymer at 60°C is more preferably at least 80 MPa, further preferably at least 130 MPa, and is more preferably at most 450 MPa, further preferably at most 350 MPa.
[0102] When the storage modulus (E') of the fluorinated copolymer is within the above range, an electrode mixture layer having further excellent flexibility can be formed.
[0103] The storage modulus (E') is a measured value obtained as follows: for a sample with a length of 30 mm, a width of 5 mm, and a thickness of 50 μm to 100 μm, the dynamic viscoelasticity apparatus DVA220 manufactured by IT Keisokuseigyo Co., Ltd. is used to measure the measured values at 30°C and 60°C under the conditions of tensile mode, clamping width of 20 mm, measuring temperature of -30°C to 160°C, heating rate of 2°C / min, and frequency of 1 Hz.
[0104] From the viewpoint of being able to form an electrode mixture layer with better adhesion and flexibility to the collector and less prone to rebound, the electrochemical device composition of the present invention preferably further contains polyvinylidene fluoride (PVdF). In particular, when the electrochemical device composition of the present invention further contains PVdF, an electrode mixture layer with lower resistance can be formed.
[0105] Polyvinylidene fluoride (PVdF) is a polymer containing units based on vinylidene fluoride (VdF) (hereinafter referred to as VdF units), and may be a VdF homopolymer consisting of only VdF units, or may contain VdF units and units based on a monomer copolymerizable with VdF.
[0106] In the above-mentioned PVdF, the monomer copolymerizable with VdF is preferably a monomer different from tetrafluoroethylene (TFE). That is, PVdF preferably does not contain a TFE unit.
[0107] In the above-mentioned PVdF, as the monomer that can be copolymerized with VdF, fluorinated monomers, non-fluorinated monomers, etc. can be mentioned, preferably fluorinated monomers. As the above-mentioned fluorinated monomers, vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), fluoroalkyl vinyl ether, hexafluoropropylene (HFP), (perfluoroalkyl) ethylene, 2,3,3,3-tetrafluoropropylene, trans-1,3,3,3-tetrafluoropropylene, etc. can be mentioned. As the above-mentioned non-fluorinated monomers, ethylene, propylene, etc. can be mentioned.
[0108] In the above PVdF, the monomer copolymerizable with VdF is preferably at least one fluorinated monomer selected from the group consisting of CTFE, fluoroalkyl vinyl ether, HFP and 2,3,3,3-tetrafluoropropylene, and more preferably at least one fluorinated monomer selected from the group consisting of CTFE, HFP and fluoroalkyl vinyl ether.
[0109] In the above-mentioned PVdF, the content of the monomer unit copolymerizable with VdF is preferably 0.10 mol% to 8.0 mol%, more preferably 0.50 mol% or more and less than 5.0 mol%, and further preferably 0.50 mol% to 3.0 mol% relative to all monomer units. In addition, the content of the above-mentioned fluorinated monomer unit is preferably 0.10 mol% to 8.0 mol%, more preferably 0.50 mol% or more and less than 5.0 mol% relative to all monomer units. In addition, the content of the monomer unit copolymerizable with VdF can be less than 1.0 mol% relative to all monomer units.
[0110] In this specification, the composition of PVdF can be, for example, 19 The results were determined by F-NMR measurement.
[0111] The above-mentioned PVdF can have a polar group, thereby, a better adhesion between the electrode composite layer and the collector can be obtained. As the above-mentioned polar group, as long as it is a polar functional group, there is no particular limitation. From the perspective of obtaining a better adhesion between the electrode composite layer and the collector, it is preferably selected from at least one of the groups consisting of a carbonyl-containing group, an epoxy group, a hydroxyl group, a sulfonic acid group, a sulfuric acid group, a phosphoric acid group, an amino group, an amide group and an alkoxy group, more preferably selected from at least one of the groups consisting of a carbonyl-containing group, an epoxy group and a hydroxyl group, and further preferably a carbonyl-containing group. The above-mentioned hydroxyl group does not include a hydroxyl group that constitutes a part of the above-mentioned carbonyl-containing group. In addition, the above-mentioned amino group refers to a univalent functional group that has removed hydrogen from ammonia, a primary amine or a secondary amine.
[0112] The above-mentioned carbonyl-containing group refers to a functional group having a carbonyl group (-C(=O)-). As the above-mentioned carbonyl-containing group, from the perspective of obtaining a better adhesion between the electrode mixture layer and the current collector, a group represented by the general formula: -COOR (R represents a hydrogen atom, an alkyl group or a hydroxyalkyl group) or a carboxylic anhydride group is preferred, and a group represented by the general formula: -COOR is more preferred. The number of carbon atoms of the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and further preferably 1 to 3. As the group represented by the general formula: -COOR, specifically, -COOCH2CH2OH, -COOCH2CH(CH3)OH, -COOCH(CH3)CH2OH, -COOH, -COOCH3, -COOC2H5, etc. can be cited. When the group represented by the general formula: -COOR is -COOH or contains -COOH, -COOH can be a carboxylate such as a metal carboxylate or an ammonium carboxylate.
[0113] As the above-mentioned amide group, preferably, a group represented by the general formula: -CO-NRR' (R and R' independently represent a hydrogen atom or a substituted or unsubstituted alkyl group) or a bond represented by the general formula: -CO-NR"- (R" represents a hydrogen atom, a substituted or unsubstituted alkyl group or a substituted or unsubstituted phenyl group).
[0114] The above-mentioned polar group can be introduced into PVdF by polymerizing VdF and a monomer having the above-mentioned polar group (hereinafter referred to as a polar group-containing monomer), or by reacting PVdF with a compound having the above-mentioned polar group. From the perspective of productivity, it is preferred to polymerize VdF and the above-mentioned polar group-containing monomer.
[0115] If VdF is polymerized with the above-mentioned polar group-containing monomer, PVdF containing VdF units and polar group-containing monomer units is obtained. That is, as PVdF, it is preferred to contain the above-mentioned polar group-containing monomer units from the perspective of obtaining a more excellent adhesion between the electrode mixture layer and the current collector. The content of the above-mentioned polar group-containing monomer units is preferably 0.001 mol% to 8.0 mol%, more preferably 0.01 mol% to 5.0 mol%, further preferably 0.10 mol% to 3.0 mol%, particularly preferably 0.15 mol% to 3.0 mol%, and most preferably 0.30 mol% to 1.5 mol%. In addition, the content of the above-mentioned polar group-containing monomer units can be less than 1.0 mol% relative to all monomer units.
[0116] In the present invention, for example, when the polar group is an acid group such as carboxylic acid, the content of the polar group-containing monomer unit in PVdF can be measured by acid-base titration of the acid group.
[0117] Examples of the above-mentioned polar group-containing monomer include: (meth) hydroxyalkyl acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; alkylidene malonates such as dimethyl methylene malonate; vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether; (meth) carboxyalkyl acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate; (meth) acryloxyalkyl dicarboxylates such as acryloxyethyl succinate, methacryloxyethyl succinate, acryloxyethyl phthalate, and methacryloxyethyl phthalate; and monoesters of unsaturated dibasic acids such as monomethyl maleate, monoethyl maleate, monomethyl citraconic acid, and monoethyl citraconic acid; General formula (2):
[0118] [Chemistry 2]
[0119]
[0120] (Where R 1 ~R 3 R independently represents a hydrogen atom, a chlorine atom or a hydrocarbon group having 1 to 8 carbon atoms. 4 represents a single bond, a hydrocarbon group having 1 to 8 carbon atoms, a heteroatom, or an atomic group having a molecular weight of 500 or less and containing at least one heteroatom selected from the group consisting of an oxygen atom, a sulfur atom, a nitrogen atom, and a phosphorus atom and having a main chain having 1 to 20 atoms. 1 represents an inorganic cation and / or an organic cation) represented by the monomer (2); etc.
[0121] Monomer (2) as a monomer (2) constituting the fluorine-containing copolymer is as described above. As the monomer containing a polar group constituting PVdF, hydroxyethyl acrylate, 2-hydroxypropyl acrylate, acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, succinic acid acryloxyethyl ester, succinic acid methacrylic acid methacrylic acid, succinic acid acryloxypropyl ester, succinic acid methacrylic acid propyl ester are preferred.
[0122] When PVdF is reacted with a compound having the above-mentioned polar group and the above-mentioned polar group is introduced into PVdF, as the compound having the above-mentioned polar group, a silane coupling agent or a titanate coupling agent containing a monomer containing the above-mentioned polar group, or PVdF and a reactive group and a hydrolyzable group can be used. As the above-mentioned hydrolyzable group, an alkoxy group is preferably used. When a coupling agent is used, the coupling agent can be added to PVdF by reacting PVdF dissolved or swollen in a solvent with the coupling agent.
[0123] As PVdF, it is also possible to use a material obtained by further reacting the partially dehydrofluorinated PVdF with an oxidant after the PVdF is partially dehydrofluorinated with an alkali. As the above-mentioned oxidant, hydrogen peroxide, hypochlorite, palladium halide, chromium halide, alkali metal permanganate, peroxide compound, alkyl peroxide, alkyl persulfate etc. can be enumerated.
[0124] About the content of the VdF unit of PVdF, from being able to obtain more excellent adhesion between the electrode mixture layer and the collector, relative to all monomer units, preferably 84.0 mol% to 99.999 mol%, more preferably 90.0 mol% or more, further preferably 92.0 mol% or more, particularly preferably 95.0 mol% or more, most preferably 97.0 mol% or more. The preferred upper limits are successively 99.99 mol% or less, 99.90 mol% or less, 99.899 mol% or less, 99.70 mol% or less, 99.50 mol% or less, 99.49 mol% or less, 99.20 mol% or less.
[0125] The weight average molecular weight (polystyrene equivalent) of PVdF is preferably 160,000 to 2,760,000, more preferably 200,000 or more, further preferably 300,000 or more, more preferably 2,530,000 or less, further preferably 2,000,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0126] The number average molecular weight (in terms of polystyrene) of PVdF is preferably 70,000 to 1,200,000, more preferably 140,000 or more, and more preferably 1,100,000 or less. The number average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0127] The melting point of PVdF is preferably 100° C. to 240° C., more preferably 130° C. to 200° C., and particularly preferably 140° C. to 180° C. The melting point can be determined as a temperature relative to a maximum value in a heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimetry (DSC) apparatus.
[0128] The average particle size of PVdF is preferably 1000 μm or less, more preferably 750 μm or less, further preferably 350 μm or less, and is preferably 0.1 μm or more, more preferably 0.2 μm or more, from the viewpoint of easily dissolving or dispersing PVdF in a solvent.
[0129] PVdF can be produced by a conventionally known method such as the following: for example, VdF is appropriately mixed with the above-mentioned polar group-containing monomer, polymerization initiator, polymerization emulsifier and other additives, and solution polymerization, suspension polymerization or emulsion polymerization is performed.
[0130] From the perspective of being able to form an electrode mixture layer that can further suppress the increase in viscosity of the electrode mixture, has better adhesion and flexibility to the collector, and is less likely to rebound, the mass ratio of the fluorinated copolymer to PVdF (fluorinated copolymer / PVdF) in the composition for electrochemical devices of the present invention is preferably 99 / 1 to 1 / 99, more preferably 95 / 5 to 3 / 97, further preferably 90 / 10 to 5 / 95, particularly preferably 70 / 30 to 7 / 93, and most preferably 50 / 50 to 10 / 90.
[0131] In addition to the fluorinated copolymer and PVdF, the electrochemical device composition of the present invention may also contain other polymers as a binder. Examples of other polymers include polymethacrylate, polymethyl methacrylate, polyacrylonitrile, polyimide, polyamide, polyamideimide, polycarbonate, styrene rubber, butadiene rubber, and the like.
[0132] From the viewpoint of being able to properly maintain the viscosity of the electrochemical device composition and obtaining high adhesion when forming an electrode mixture layer, the content of the binder in the electrochemical device composition of the present invention is preferably 0.01% by mass to 10% by mass, more preferably 0.2% by mass to 5.0% by mass, further preferably 0.5% by mass to 3.0% by mass, and particularly preferably 0.8% by mass to 2.5% by mass relative to the mass of the composition. When the content of the binder is within the above range, the electrochemical device composition has a moderate viscosity, and an electrode mixture in which each component is fully dispersed can be prepared without applying excessive shear force. Therefore, in the obtained electrode mixture layer, a three-dimensional network of single-layer carbon nanotubes is fully formed, which can take into account the better adhesion between the electrode mixture layer and the collector and the better flexibility of the electrode structure.
[0133] The optical concentration (optical density) of the composition for electrochemical devices of the present invention is preferably 0.3 to 0.7 absorbance units, more preferably 0.40 to 0.65 absorbance units, and further preferably 0.42 to 0.62 absorbance units. The optical concentration is obtained by measuring the absorption of light of a wavelength of 500 nm using a spectrophotometer cell with an optical path length of 10 mm for a solution containing 0.001 mass % of single-walled carbon nanotubes as a reference, using an NMP solution.
[0134] The electrochemical device composition of the present invention is diluted or concentrated as needed, thereby adjusting the concentration of the single-layer carbon nanotubes to 0.001% by mass. If the absorption of light with a wavelength of 500nm brought by the obtained solution is within the above range, the dispersibility of the electrode mixture is excellent, and the electrode mixture can be prepared without applying excessive shear force. Therefore, the three-dimensional network structure of the single-layer carbon nanotubes can be fully formed in the obtained electrode mixture layer, and the adhesion of the electrode mixture layer to the collector and the flexibility of the electrode structure can be taken into account.
[0135] Solvents
[0136] The composition for electrochemical devices of the present invention further contains a solvent. As the solvent, an organic solvent is preferred, and examples thereof include nitrogen-containing organic solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and dimethylformamide; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ester solvents such as ethyl acetate and butyl acetate; ether solvents such as tetrahydrofuran and dioxane; β-alkoxypropionamides such as β-methoxy-N,N-dimethylpropionamide, β-n-butoxy-N,N-dimethylpropionamide, and β-n-hexyloxy-N,N-dimethylpropionamide; and low-boiling-point general-purpose organic solvents such as mixed solvents thereof. Among them, as a solvent, from the perspective of excellent coating properties, at least one selected from the group consisting of N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone and β-alkoxypropionamides is preferred, and at least one selected from the group consisting of N-methyl-2-pyrrolidone and N,N-dimethylacetamide is more preferred.
[0137] The viscosity of the composition for electrochemical devices of the present invention is preferably 5mPa·s to 8000mPa·s, more preferably 100mPa·s to 5000mPa·s, and further preferably 100mPa·s to 2000mPa·s. The above viscosity is measured using a B-type viscometer (manufactured by Brookfield, LV-DV2T) at 25°C, rotor No. SC4-21, and a rotation speed of 20rpm. When the viscosity of the composition for electrochemical devices of the present invention is within the above range, an electrode mixture in which each component is fully dispersed can be prepared without applying excessive shear force. Therefore, in the obtained electrode mixture layer, a three-dimensional network of single-layer carbon nanotubes is fully formed, and at the same time, it is possible to take into account both the better adhesion between the electrode mixture layer and the collector and the better flexibility of the electrode structure.
[0138] The composition for electrochemical devices of the present invention is a composition for forming a component constituting an electrochemical device. As an electrochemical device, there is no particular limitation as long as it is a device for converting electrical energy and chemical energy, and lithium ion secondary batteries, lithium ion capacitors, hybrid capacitors, double electric layer capacitors, aluminum electrolytic capacitors, etc. can be cited. As an electrochemical device, lithium ion secondary batteries or lithium ion capacitors are preferred. As a component of an electrochemical device, for example, electrodes, diaphragms, etc. can be cited. Among them, the composition for electrochemical devices of the present invention is preferably used to form an electrode of a lithium ion secondary battery or a lithium ion capacitor. The composition for electrochemical devices of the present invention can be used, for example, to form a positive electrode mixture layer, a negative electrode mixture layer, a conductive layer or an adhesive layer (primer) disposed between the positive electrode mixture layer and the collector, a conductive layer or an adhesive layer (primer) disposed between the negative electrode mixture layer and the collector, etc. In addition, the electrochemical device composition of the present invention can obtain a positive electrode mixture whose viscosity is not easy to rise even after a long time after preparation, and can form a positive electrode mixture layer with low resistance, and can form a positive electrode mixture layer with excellent adhesion and flexibility to the collector and difficult to rebound, so it is more preferably used to form a positive electrode of a lithium ion secondary battery, and further preferably used to form a positive electrode mixture layer of a positive electrode of a lithium ion secondary battery. The electrochemical device composition of the present invention preferably does not contain a positive electrode active material, and can be distinguished from the positive electrode mixture described later in that it does not contain a positive electrode active material.
[0139] The composition for an electrochemical device of the present invention can be prepared by mixing the components. The order of mixing the components is not particularly limited. For example, the composition for an electrochemical device can be prepared by mixing the single-walled carbon nanotubes and a solvent, and then mixing the resulting dispersion with a binder.
[0140] A known stirrer can be used for mixing. In addition, by using a homogenizer, a composition for an electrochemical device in which the single-walled carbon nanotubes and the binder are uniformly dispersed in a solvent can be easily obtained.
[0141] As a homogenizer, a rotary homogenizer, an ultrasonic homogenizer, a high-pressure homogenizer, etc. can be used. The output power of the ultrasonic homogenizer can be 5kW to 50kW. The energy applied to the dispersion or the electrochemical device composition by the ultrasonic homogenizer can be 0.1kWh to 1kWh per 1kg of the dispersion or the electrochemical device composition. The pressure during mixing by the high-pressure homogenizer can be 100 bar to 2000 bar. The dispersion or the electrochemical device composition can be passed through the high-pressure homogenizer multiple times, and can be passed through 2 to 20 times.
[0142] The composition for electrochemical devices of the present invention can be prepared, for example, by the following method: after mixing the single-walled carbon nanotubes and the solvent using an ultrasonic homogenizer, the obtained dispersion is mixed with the binder using a high-pressure homogenizer. The single-walled carbon nanotubes and the solvent can be mixed using an ultrasonic homogenizer while being stirred using a stirrer.
[0143] Positive electrode mixture
[0144] The positive electrode mixture of the present invention contains the above-mentioned electrochemical device composition and positive electrode active material. Therefore, the positive electrode mixture of the present invention contains the single-layer carbon nanotubes, binder and solvent contained in the above-mentioned electrochemical device composition, and positive electrode active material. The positive electrode mixture of the present invention is not easy to increase in viscosity even after a long time after preparation, and can form a positive electrode mixture layer with low resistance, and can form an electrode mixture layer with excellent adhesion and flexibility with the collector and difficult to rebound.
[0145] The content of single-walled carbon nanotubes in the positive electrode mixture of the present invention can be 0.001 to 10 parts by mass, preferably 0.001 to 2 parts by mass, more preferably 0.005 parts by mass or more, further preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, more preferably 1.0 parts by mass or less, further preferably 0.2 parts by mass or less, and particularly preferably 0.1 parts by mass or less, relative to 100 parts by mass of the positive electrode active material.
[0146] The content of the binder in the positive electrode mixture of the present invention is preferably 0.1 to 5.0 parts by mass, more preferably 0.3 or more parts by mass, further preferably 0.5 or more parts by mass, more preferably 3.0 or less parts by mass, and further preferably 2.0 or less parts by mass, relative to 100 parts by mass of the positive electrode active material. If the binder in the positive electrode mixture of the present invention contains a fluorinated copolymer, it may contain only a fluorinated copolymer, or it may contain a fluorinated copolymer and PVdF. From the perspective of being able to further suppress the viscosity increase of the positive electrode mixture, being able to form a positive electrode mixture layer with better adhesion and flexibility with the collector, and being more difficult to rebound, the mass ratio of the fluorinated copolymer to PVdF (fluorinated copolymer / PVdF) when the binder contains a fluorinated copolymer and PVdF is preferably 99 / 1 to 1 / 99, more preferably 95 / 5 to 3 / 97, further preferably 90 / 10 to 5 / 95, particularly preferably 70 / 30 to 7 / 93, and most preferably 50 / 50 to 10 / 90.
[0147] Positive active material
[0148] There are no particular restrictions on the positive electrode active material as long as it can electrochemically absorb and release lithium ions. The positive electrode active material preferably contains lithium and at least one transition metal, such as lithium transition metal composite oxides and lithium-containing transition metal phosphate compounds.
[0149] As the transition metal of the lithium transition metal composite oxide, V, Ti, Cr, Mn, Fe, Co, Ni, Cu and the like are preferred. As specific examples of the lithium transition metal composite oxide, there can be mentioned lithium·cobalt composite oxides such as LiCoO2; lithium·nickel composite oxides such as LiNiO2; lithium·manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO3, etc. The transition metal atoms as the main body of these lithium transition metal composite oxides are partially replaced by other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, etc. As the substances obtained by the above replacement, there can be mentioned lithium·nickel·manganese composite oxides, lithium·nickel·cobalt·aluminum composite oxides, lithium·nickel·cobalt·manganese composite oxides, lithium·manganese·aluminum composite oxides, lithium·titanium composite oxides and the like. As specific examples of the replaced substances, there can be mentioned LiNi 0.5 Mn 0.5 O2、LiNi 0.85 Co 0.10 Al 0.05 O2、LiNi 0.82 Co 0.15 Al 0.03 O2、LiNi 0.80 Co 0.15 Al 0.05 O2、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiMn 1.8 Al 0.2 O4、LiMn 1.5 Ni 0.5 O4、Li4Ti5O 12 wait.
[0150] As the transition metal of the lithium-containing transition metal phosphate compound, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. As specific examples of the lithium-containing transition metal phosphate compound, there can be cited iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7; cobalt phosphates such as LiCoPO4; and substances obtained by replacing part of the transition metal atoms that are the main body of these lithium-containing transition metal phosphate compounds with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.
[0151] As the positive electrode active material, from the perspective of obtaining a battery with excellent output characteristics, cycle characteristics and 60°C storage characteristics, it is preferably selected from at least one of the group consisting of lithium·cobalt composite oxides, lithium·nickel composite oxides, lithium·manganese composite oxides, iron phosphates, lithium·nickel·manganese composite oxides, lithium·nickel·cobalt·manganese composite oxides and lithium·nickel·cobalt·aluminum composite oxides, and more preferably selected from the group consisting of LiCoO2, LiNiO2, LiMn2O4, LiFePO4, LiNi 0.33 Mn 0.33 Co 0.33 O2、LiNi 0.5 Mn 0.3 Co 0.2 O2、LiNi 0.82 Co 0.15 Al 0.03 O2、LiNi 0.6 Mn 0.2 Co 0.2 O2、LiNi 0.8 Mn 0.1 Co 0.1 O2 and LiNi 0.90 Mn 0.05 Co 0.05 At least one of the group consisting of O2.
[0152] The positive electrode active material may be a lithium-nickel composite oxide or a general formula (1): Li y Ni 1-x M x O2
[0153] (wherein, x satisfies 0.01≤x≤0.5, y satisfies 0.9≤y≤1.2, and M represents a metal atom (excluding Ni)) is a lithium-nickel composite oxide. Such a positive electrode active material containing a large amount of Ni is beneficial to the high capacity of secondary batteries. The positive electrode mixture of the present invention does not easily increase viscosity even when it contains a large amount of positive electrode active material containing Ni, and can form a positive electrode mixture layer with low resistance, and at the same time can form a positive electrode mixture layer that is excellent in both adhesion to the collector and flexibility and is difficult to rebound.
[0154] In the general formula (1), x is a coefficient satisfying 0.01≤x≤0.5, and is preferably 0.05≤x≤0.4, and more preferably 0.10≤x≤0.3, from the viewpoint of obtaining a secondary battery with a higher capacity.
[0155] In the general formula (1), examples of the metal atom of M include V, Ti, Cr, Mn, Fe, Co, Cu, Al, Zn, Mg, Ga, Zr, Si, etc. The metal atom of M is preferably a transition metal such as V, Ti, Cr, Mn, Fe, Co, Cu, or a combination of the above transition metals with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Cu, Zn, Mg, Ga, Zr, Si, etc.
[0156] As the lithium-nickel composite oxide represented by the general formula (1), it is preferable to select LiNi 0.82 Co 0.15 Al 0.03 O2、LiNi 0.6 Mn 0.2 Co 0.2 O2、LiNi 0.8 Mn 0.1 Co 0.1 O2 and LiNi 0.90 Mn 0.05 Co 0.05 At least one of the group consisting of O2, more preferably selected from LiNi 0.82 Co 0.15 Al 0.03 O2 and LiNi 0.8 Mn 0.1 Co 0.1 At least one of the group consisting of O2.
[0157] A different positive electrode active material may be used in combination with the lithium-nickel composite oxide represented by the general formula (1). Specifically, different positive electrode active materials include LiCoO2, LiMnO2, LiMn2O4, Li2MnO3, LiMn 1.8 Al 0.2 O4、Li4Ti5O 12 , LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, LiCoPO4, Li 1.2 Fe 0.4 Mn 0.4 O2, LiNiO2, LiNi 0.5 Mn 0.3 Co 0.2 O2, etc.
[0158] In addition, as the positive electrode active material, a positive electrode active material having a material composition different from that of the positive electrode active material as the main body attached to the surface of the positive electrode active material can also be used. Examples of the surface-attached material include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, and carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate.
[0159] These surface-attached substances can be attached to the surface of the positive electrode active material by, for example, the following methods: a method of dissolving or suspending the substance in a solvent, adding the substance to the positive electrode active material by infiltration and drying; a method of dissolving or suspending the surface-attached substance precursor in a solvent, adding the substance to the positive electrode active material by infiltration and then reacting the substance by heating or the like; a method of adding the substance to the positive electrode active material precursor and simultaneously firing the substance; and the like.
[0160] The amount of the surface-attached substance is preferably 0.1 ppm or more, more preferably 1 ppm or more, further preferably 10 ppm or more, preferably 20% or less, more preferably 10% or less, and further preferably 5% or less relative to the positive electrode active material by mass. The surface-attached substance can inhibit the oxidation reaction of the non-aqueous electrolyte on the surface of the positive electrode active material and improve the battery life; however, if the amount of the surface-attached substance is too small, the effect cannot be fully demonstrated; if the amount of the surface-attached substance is too large, the entry and exit of lithium ions will be hindered, so the resistance may increase.
[0161] The shape of the positive electrode active material particles can use the previously used block, polyhedron, spherical, ellipsoidal, plate-like, needle-like, columnar, etc., wherein the following positive electrode active material particles are preferably formed by agglomeration of primary particles to form secondary particles, and the shape of the secondary particles is spherical or ellipsoidal. Usually in electrochemical elements, along with its charging and discharging, the active material in the electrode expands and shrinks, so it is easy to cause the destruction of the active material or the disconnection of the conductive path caused by its stress. Therefore, compared with a single particle active material with only primary particles, the material formed by the agglomeration of primary particles to form secondary particles can alleviate the stress of expansion and contraction and prevent degradation, so it is preferred. In addition, compared with particles with plate-like equiaxial orientation, in the case of spherical or ellipsoidal particles, the orientation during electrode molding is less, so the expansion and contraction of the electrode during charging and discharging is also less, and it is also easy to mix evenly with the conductive agent when making the electrode, so it is preferred.
[0162] The tap density of the positive electrode active material is usually 1.3 g / cm 3 Above, preferably 1.5 g / cm 3 More preferably, 1.6 g / cm 3More than, most preferably 1.7g / cm 3 Above. If the tap density of the positive electrode active material is less than the above lower limit, the amount of dispersion medium required when the positive electrode active material layer is formed increases, and at the same time, the required amount of conductive additive or binder increases. Sometimes, the filling rate of the positive electrode active material in the positive electrode mixture layer is limited, and the battery capacity is limited. By using a positive electrode active material with a high tap density, a high-density positive electrode mixture layer can be formed. The larger the tap density is, the better, and there is no particular upper limit. However, if it is too large, the diffusion of lithium ions in the positive electrode mixture layer with the non-aqueous electrolyte as the medium becomes rate-limiting, and sometimes the load characteristics are easily reduced. Therefore, it is usually 2.5g / cm 3 Below, preferably 2.4 g / cm 3 the following.
[0163] The tap density of the positive electrode active material was determined by passing the sample through a sieve with a mesh size of 300 μm and dropping the sample to a depth of 20 cm. 3 The powder is placed in a tapping cell and filled to the capacity. A powder density meter (e.g. Tap Denser manufactured by Seishin Enterprise) is then used to perform 1000 oscillations with a stroke length of 10 mm. The density is calculated from the volume and weight of the sample at this time and is defined as the tap density.
[0164] The median diameter d50 of the particles of the positive electrode active material (secondary particle diameter in the case where the primary particles are agglomerated to form secondary particles) is usually 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and most preferably 3 μm or more; usually 20 μm or less, preferably 18 μm or less, more preferably 16 μm or less, and most preferably 15 μm or less. If it is less than the above lower limit, a high bulk density product may not be obtained; if it exceeds the upper limit, the diffusion of lithium in the particles takes time, which may cause a decrease in battery performance, or when the positive electrode of the battery is made, that is, the positive electrode active material and the conductive auxiliary agent, the binder, etc. are made into a slurry using a solvent and applied in a thin film, stripes and other problems may sometimes occur. Here, by mixing two or more positive electrode active materials with different median diameters d50, the filling property during the production of the positive electrode can be further improved.
[0165] It should be noted that the median diameter d50 in the present invention is measured using a known laser diffraction / scattering particle size distribution measuring device. When using LA-920 manufactured by HORIBA as a particle size distribution meter, as the dispersion medium used during measurement, a 0.1% by mass sodium hexametaphosphate aqueous solution is used, and after 5 minutes of ultrasonic dispersion, the measured refractive index is set to 1.24 for measurement.
[0166] In the case where the primary particles are condensed to form secondary particles, the average primary particle size of the positive electrode active material is usually 0.01 μm or more, preferably 0.05 μm or more, more preferably 0.08 μm or more, and most preferably 0.1 μm or more; usually 3 μm or less, preferably 2 μm or less, more preferably 1 μm or less, and most preferably 0.6 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, which has an adverse effect on the powder filling property, or the specific surface area is greatly reduced, so the possibility of reduced battery performance such as output characteristics sometimes increases. On the contrary, if it is less than the lower limit, it is usually sometimes due to poor reversibility of charge and discharge due to underdeveloped crystallization. It should be noted that the primary particle size is measured by observation using a scanning electron microscope (SEM). Specifically, in a photograph with a magnification of 10,000 times, the longest value of the slice obtained by the left and right boundary lines of the primary particles relative to the straight line in the horizontal direction is obtained for any 50 primary particles, and the average value is taken to obtain the primary particle size.
[0167] The BET specific surface area of the positive electrode active material is usually 0.2 m 2 / g or more, preferably 0.3m 2 / g or more, more preferably 0.4m 2 / g or more, usually 4.0m 2 / g or less, preferably 2.5m 2 / g or less, more preferably 1.5m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to be reduced; if the BET specific surface area is larger than this range, the tap density is difficult to increase, and the coating properties of the positive electrode mixture may be problematic.
[0168] The BET specific surface area is defined as follows: Using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken Co., Ltd.), pre-dry the sample at 150°C for 30 minutes under nitrogen flow, and then use a nitrogen-helium mixed gas accurately adjusted to a relative pressure of 0.3 relative to atmospheric pressure to perform the measurement by the nitrogen adsorption BET single-point method based on the gas flow method, and use the obtained value to define the BET specific surface area.
[0169] As a method for manufacturing positive electrode active materials, a common method for manufacturing inorganic compounds is used. In particular, various methods are considered for preparing spherical or ellipsoidal active materials, for example, the following methods can be cited: a transition metal raw material such as a transition metal nitrate, sulfate, etc. and a raw material of other elements as required are dissolved or crushed and dispersed in a solvent such as water, pH is adjusted under stirring, a spherical precursor is prepared and recovered, and it is dried as required, and then a Li source such as LiOH, Li2CO3, LiNO3 is added and fired at a high temperature to obtain an active material; a transition metal raw material such as a transition metal nitrate, sulfate, hydroxide, oxide, etc. and a raw material of other elements as required are dissolved or crushed and dispersed in water A method in which a raw material of a transition metal such as a nitrate of a transition metal, a sulfate of a transition metal, a hydroxide of a transition metal oxide, a Li source such as LiOH, Li2CO3, LiNO3, and other elements as required are dissolved or crushed and dispersed in a solvent such as water, dried and molded by a spray dryer to make a spherical or ellipsoidal precursor, and then fired at a high temperature to obtain an active material; and the like.
[0170] It should be noted that the positive electrode active material may be used alone or in any combination and proportion.
[0171] Conductive additives
[0172] In order to form a positive electrode capable of realizing an electrochemical device exhibiting higher energy density, the positive electrode mixture of the present invention preferably does not contain a conductive additive other than the single-walled carbon nanotubes.
[0173] In addition, from the perspective of being able to form a positive electrode that can achieve excellent output characteristics and cycle characteristics of an electrochemical device, the positive electrode mixture of the present invention preferably further contains a conductive additive other than the single-layer carbon nanotube. As the above-mentioned conductive additive, carbon blacks such as acetylene black and ketjen black or carbon materials such as graphite and graphene, carbon fibers, multilayer carbon nanotubes, carbon nanotubes, etc. can be cited.
[0174] The content of the conductive aid (excluding single-walled carbon nanotubes) in the positive electrode mixture of the present invention is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, and even more preferably 0.1 to 1.0 parts by mass, relative to 100 parts by mass of the positive electrode active material.
[0175] additive
[0176] In order to suppress the increase in viscosity of the positive electrode mixture, the positive electrode mixture may further contain additives such as organic acids and carboxylic acids. Among them, the positive electrode mixture preferably contains an organic acid.
[0177] Examples of the organic acid include acrylic acid, formic acid, citric acid, acetic acid, oxalic acid, lactic acid, pyruvic acid, malonic acid, propionic acid, maleic acid, citraconic acid, and butyric acid.
[0178] The content of the additive in the positive electrode mixture is preferably 0.001% to 5% by mass, more preferably 0.005% by mass or more, further preferably 0.01% by mass or more, more preferably 3% by mass or less, further preferably 2% by mass or less relative to the total mass of the binder and the positive electrode active material. By making the content of the additive within the above range, the viscosity increase of the positive electrode mixture can be further suppressed.
[0179] In order to improve the viscosity stability of the positive electrode mixture, the positive electrode mixture may contain anionic surfactants, cationic surfactants, nonionic surfactants, methyl cellulose, carboxymethyl cellulose, hydroxypropyl methyl cellulose, polyacrylic acid, polymethyl methacrylate, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile, etc.
[0180] Since coating is easy and a positive electrode mixture layer with a desired thickness is easily obtained, the viscosity of the positive electrode mixture is preferably 1000mPa·s to 80000mPa·s, more preferably 2000mPa·s to 70000mPa·s, and further preferably 3000mPa·s to 60000mPa·s. The above viscosity is measured using a B-type viscometer (manufactured by Brookfield, LV-DV2T) at 25°C, rotor No. LV-4, and a rotation speed of 6rpm.
[0181] The content of the single-walled carbon nanotubes, binder, positive electrode active material, solvent and optionally contained conductive auxiliary agent in the positive electrode mixture is determined in consideration of the coating property on the collector, the film forming property after drying, etc. The total content of the single-walled carbon nanotubes, binder, positive electrode active material and optionally contained conductive auxiliary agent in the positive electrode mixture is preferably 50 mass % to 90 mass %, more preferably 60 mass % to 80 mass %.
[0182] The positive electrode mixture of the present invention can be prepared by mixing the components. At this time, the order of mixing the components is not particularly limited. For example, when the electrochemical device composition of the present invention does not contain PVdF, the electrochemical device composition of the present invention can be mixed with PVdF, and then other components such as a positive electrode active material can be mixed. It is also possible to mix the electrochemical device composition of the present invention with a positive electrode active material and then other components such as PVdF.
[0183] Positive electrode structure
[0184] The positive electrode structure of the present invention comprises a current collector and a positive electrode mixture layer. The positive electrode mixture layer is formed using the above-mentioned positive electrode mixture and can be provided on one side or both sides of the positive electrode current collector.
[0185] The density of the positive electrode mixture layer is preferably 3.0 g / cm 3 ~5.0g / cm 3 , more preferably 3.2 g / cm 3 ~5.0g / cm 3 , more preferably 3.5 g / cm 3 ~5.0g / cm 3 The existing high-density positive electrode mixture layer sometimes increases in thickness during heat treatment (springback). Since the positive electrode mixture layer of the positive electrode structure of the present invention is formed using the above-mentioned positive electrode mixture, springback is unlikely to occur even if the density of the positive electrode mixture layer is high, and the flexibility is also excellent.
[0186] The density of the positive electrode mixture layer can be calculated from the mass and volume of the positive electrode mixture layer.
[0187] The thickness of the positive electrode mixture layer is preferably 20 μm or more, more preferably 45 μm or more, further preferably 70 μm or more, particularly preferably 75 μm or more, and most preferably 80 μm or more, and preferably 170 μm or less, and more preferably 150 μm or less. The positive electrode mixture layer formed using the positive electrode mixture of the present invention has excellent flexibility even when the thickness is relatively large.
[0188] The thickness of the positive electrode mixture layer can be measured using a micrometer. When the positive electrode mixture layer is provided on both sides of the positive electrode current collector, the thickness of the positive electrode mixture layer in the present invention is the thickness per single side.
[0189] Since the viscosity increase of the positive electrode mixture can be further suppressed, a positive electrode mixture layer with lower resistance, better adhesion and flexibility to the collector, and less prone to rebound can be formed. The content of the positive electrode active material in the positive electrode mixture layer is preferably 96.0 mass% to 99 mass%, more preferably 96.5 mass% to 98.9 mass%, and further preferably 97.0 mass% to 98.8 mass%, relative to the mass of the positive electrode mixture layer.
[0190] Current Collector
[0191] The positive electrode structure of the present invention includes a current collector. Examples of the current collector of the positive electrode structure of the present invention include metal foils or metal meshes made of iron, stainless steel, copper, aluminum, nickel, titanium, and the like, and aluminum foil is preferred.
[0192] Method for manufacturing positive electrode structure
[0193] The positive electrode structure of the present invention can be suitably manufactured by the following manufacturing method, which comprises: a step of preparing a positive electrode mixture containing at least a single-walled carbon nanotube, a binder, a solvent and a positive electrode active material; and a step of applying the obtained positive electrode mixture to a current collector. After applying the positive electrode mixture, the coating film can be further dried and the obtained dried coating film can be pressed.
[0194] The coating amount of the positive electrode mixture on the current collector is preferably 20 mg / cm2 in order to achieve a high capacity of the lithium ion secondary battery. 2 More preferably 22 mg / cm 2 More preferably, 25 mg / cm 2 Above, particularly preferably 28 mg / cm 2 From the perspective of suppressing cracks in the positive electrode mixture layer, 60 mg / cm 2 Less than 50 mg / cm 2 Below. The coating amount of the positive electrode mixture is the dry weight of the positive electrode mixture per unit area. Even if a relatively large amount of the positive electrode mixture of the present invention is applied to the collector to form a relatively thick positive electrode mixture layer, the resulting positive electrode mixture layer has excellent softness. In addition, even if a relatively large amount of the positive electrode mixture of the present invention is applied to the collector and pressed at a high pressure to form a high-density positive electrode mixture layer, it is difficult to rebound.
[0195] Secondary battery
[0196] In addition, according to the present invention, a secondary battery having the above-mentioned positive electrode structure is provided. The secondary battery of the present invention preferably has a negative electrode structure and a non-aqueous electrolyte in addition to the above-mentioned positive electrode structure. Since the secondary battery of the present invention has the above-mentioned positive electrode structure, it has excellent output characteristics, cycle characteristics and 60°C storage characteristics.
[0197] The non-aqueous electrolyte is not particularly limited, and one or more of the known solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, etc. can be used. The electrolyte can also use all existing known substances, and can use LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc.
[0198] The positive electrode structure of the present invention has excellent flexibility and the positive electrode mixture layer and the current collector are sufficiently adhered to each other, so it can be suitably used as a positive electrode structure for a wound-type secondary battery. In addition, the secondary battery of the present invention may be a wound-type secondary battery.
[0199] The positive electrode structure of the present invention is useful not only for the lithium ion secondary battery using a liquid electrolyte as described above as a non-aqueous electrolyte secondary battery, but also for a polymer electrolyte lithium secondary battery and also for an electric double layer capacitor.
[0200] Although the embodiments have been described above, it should be understood that various changes may be made to the embodiments and details without departing from the spirit and scope of the claims.
[0201] Example
[0202] Next, embodiments of the present invention will be described with reference to examples, but the present invention is not limited to the above examples.
[0203] Each numerical value in the examples was measured by the following method.
[0204] <Composition of fluorinated copolymer>
[0205] (Ratio of VdF units to TFE units)
[0206] The ratio of the VdF unit to the TFE unit was determined by NMR analysis of a DMF-d7 solution of the fluorinated copolymer (manufactured by Agilent Technologies, VNS 400 MHz). 19 The results were determined by F-NMR measurement.
[0207] pass 19 The following peak areas (A, B, C, and D) were determined by F-NMR measurement, and the ratio of the VdF unit to the TFE unit was calculated.
[0208] A: The area of the peak between -86ppm and -98ppm
[0209] B: The area of the peak between -105ppm and -118ppm
[0210] C: The area of the peak at -119 ppm to -122 ppm
[0211] D: The area of the peak between -122ppm and -126ppm
[0212] Ratio of VdF units: (4A+2B) / (4A+3B+2C+2D)×100 [mol %]
[0213] Ratio of TFE units: (B + 2C + 2D) / (4A + 3B + 2C + 2D) × 100 [mol%]
[0214] (Ratio of VdF units to HFP units and ratio of VdF units to PMVE units)
[0215] Regarding the ratio of VdF units to HFP units and the ratio of VdF units to PMVE units, using an NMR analyzer (manufactured by Agilent Technologies, VNS400MHz), through 19 F-NMR measurement of the DMF-d7 solution of the fluorine-containing copolymer.
[0216] (Content of monomer units containing polar groups)
[0217] Regarding the content of monomer units containing polar groups (4-pentenoic acid units, 3-butenoic acid units, acrylic acid units, etc.) in the fluorine-containing copolymer, it is determined by acid-base titration of carboxyl groups. Dissolve approximately 0.5 g of the fluorine-containing copolymer in acetone at a temperature of 70°C to 80°C. To avoid solidification of the fluorine-containing copolymer, add 5 ml of water. Conduct titration with an aqueous NaOH solution having a concentration of 0.1 N until complete neutralization of the acidity with a neutral transfer at approximately -270 mV. Based on the measured acid equivalent, determine the amount of the monomer units containing polar groups contained in 1 g of the fluorine-containing copolymer, and calculate the content of the monomer units containing polar groups.
[0218] <Composition of PVdF>
[0219] (Content of monomer units containing polar groups)
[0220] The content of monomer units containing polar groups (acrylic acid units, maleic acid units, 3-butenoic acid units, etc.) in PVdF is determined by acid-base titration of carboxyl groups. Dissolve approximately 0.5 g of PVdF in acetone at a temperature of 70°C to 80°C. To avoid solidification of PVdF, add 5 ml of water. Conduct titration with an aqueous NaOH solution having a concentration of 0.1 N until complete neutralization of the acidity with a neutral transfer at approximately -270 mV. Based on the measured acid equivalent, determine the amount of the monomer units containing polar groups contained in 1 g of PVdF from the measurement results, and calculate the content of the monomer units containing polar groups.
[0221] <Weight-average molecular weight>
[0222] The measurement was performed by gel permeation chromatography (GPC). AS-8010 and CO-8020 columns (three GMHHR-H columns connected in series) manufactured by Tosoh Corporation and RID-10A manufactured by Shimadzu Corporation were used, and dimethylformamide (DMF) as a solvent was passed at a flow rate of 1.0 ml / min, and the value was calculated from the measured data (reference: polystyrene).
[0223] <Melting point>
[0224] Using a differential scanning calorimetry (DSC) apparatus, the temperature was raised from 30°C to 220°C at a rate of 10°C / min, then lowered to 30°C at 10°C / min, and again raised to 220°C at a rate of 10°C / min, and the temperature corresponding to the maximum value in the heat of fusion curve at this time was determined as the melting point.
[0225] <Storage modulus (E')>
[0226] The storage modulus is a value measured at 30°C or 60°C by dynamic viscoelasticity measurement, and is measured using a dynamic viscoelasticity apparatus DVA220 manufactured by IT Keisokuseigyo Co., Ltd., for a test piece having a length of 30 mm, a width of 5 mm, and a thickness of 50 μm to 100 μm, in a tensile mode, a clamping width of 20 mm, a measuring temperature of -30°C to 160°C, a heating rate of 2°C / min, and a frequency of 1 Hz.
[0227] The test piece used in the measurement was prepared as follows: the fluorinated copolymer was dissolved in N-methyl-2-pyrrolidone (NMP) at a concentration of 10% to 20% by mass, the obtained fluorinated copolymer solution was cast onto a glass plate and dried at 100°C for 12 hours, and then dried at 100°C for 12 hours under vacuum, and the obtained film with a thickness of 50 μm to 100 μm was cut into a length of 30 mm and a width of 5 mm, thereby preparing a test piece.
[0228] <Viscosity>
[0229] The viscosity of the composition was measured using a B-type viscometer (Brookfield, LV-DV2T) at 25°C, rotor No. SC4-21, and a rotation speed of 20 rpm, and the measured value after 10 minutes from the start of the measurement was taken as the viscosity. The viscosity of the positive electrode mixture was measured using a B-type viscometer (Brookfield, LV-DV2T) at 25°C, rotor No. LV-4, and a rotation speed of 6 rpm, and the measured value after 10 minutes from the start of the measurement was taken as the viscosity.
[0230] <Stability of positive electrode mixture>
[0231] The viscosity of the mixture at the time of preparation (η0) and the viscosity 24 hours after preparation (ηn) were measured, and the viscosity change rate (Xn) was calculated by the following formula.
[0232] Xn=ηn / η0×100[%]
[0233] Based on the obtained viscosity change rate (Xn), evaluation was performed according to the following criteria.
[0234] ○: Xn is less than 200%
[0235] △: Xn exceeds 200% and is less than 300%
[0236] ×: Xn exceeds 300%
[0237] If a positive electrode mixture with a viscosity change rate (Xn) of 200% or less is used, a positive electrode showing good characteristics can be produced. If a positive electrode mixture with a viscosity change rate (Xn) exceeding 200% and below 300% is used, it will be difficult to form a positive electrode mixture layer with a smooth surface. Positive electrode mixtures with a viscosity change rate (Xn) exceeding 300% are difficult to apply.
[0238] <Density of Positive Electrode Mixture Layer>
[0239] The double-sided coated positive electrode structure obtained by pressing with a roller press was cut to prepare a test piece, and the mass and area of the test piece were measured. In addition, the density of the positive electrode mixture layer was calculated from the mass of the test piece and the positive electrode collector, the area of the test piece, and the thickness of the positive electrode mixture layer measured by a micrometer.
[0240] <Film resistance>
[0241] The positive electrode mixture was applied onto a PET film using a doctor blade and then dried, and the surface resistance of the coating film was measured. Loresta-GP (manufactured by Mitsubishi Chemical Analytical Tech Co., Ltd.) (compliant with JIS K7194) was used for the measurement.
[0242] <Adhesion between positive electrode mixture layer and current collector>
[0243] The single-sided coated positive electrode structure obtained by pressing with a roller press was cut to produce a 1.2 cm × 7.0 cm test piece. After the electrode side of the test piece was fixed to a movable fixture with double-sided tape, the tape was attached to the surface of the positive electrode collector, and the tape was stretched 90 degrees at a speed of 100 mm / min. The stress (N / cm) at this time was measured using an autograph. The force sensor of the autograph used 50N.
[0244] <Positive electrode flexibility>
[0245] The double-sided coated positive electrode structure obtained by pressing using a roll press was cut to prepare a test piece of 2 cm×20 cm.
[0246] A cylindrical mandrel bending tester (manufactured by Allgood) was used. The test piece was clamped and fixed to the tester with a mandrel having a diameter of 3 mm using the main body chuck. Then, a roller was brought close to the test piece. The positive electrode mixture layer was visually confirmed when the handle was evenly rotated 180° in 1 to 2 seconds. Evaluation was performed according to the following criteria.
[0247] ○: No cracks were observed.
[0248] △: Cracks were observed, but no breakage of the positive electrode mixture layer was observed.
[0249] ×: The positive electrode mixture layer is broken.
[0250] <Rebound>
[0251] For the double-sided coated positive electrode structure obtained by pressing using a roller press, a manual punch with a size of Φ13mm was used to punch out and produce a test piece, and the mass and area of the test piece were measured. Then, the density of the positive electrode mixture layer was calculated from the mass of the test piece and the positive electrode collector, the area of the test piece, and the thickness of the positive electrode mixture layer measured by a micrometer, and it was used as the density (D0). After the test piece was dried in a vacuum dryer at 120°C for 12 hours, the density of the positive electrode mixture layer was calculated in the same way as the density (D n ) The springback rate (Y n ) Preferably, the greater the rebound rate, the less the density reduction of the positive electrode mixture layer due to the heat treatment.
[0252] Y n =D n / D0×100(%)
[0253] In Examples and Comparative Examples, the following polymers were used.
[0254] <Fluorinated copolymer (A)>
[0255] (A-1): Fluorinated copolymer containing VdF units and TFE units
[0256] VdF / TFE=81 / 19 (mol%)
[0257] Weight average molecular weight 1230000
[0258] Melting point 128℃
[0259] Storage modulus at 30°C: 510MPa
[0260] Storage modulus at 60°C: 270MPa
[0261] (A-2): Fluorinated copolymer containing VdF units, TFE units and 4-pentenoic acid units
[0262] VdF / TFE=62 / 38 (mol%)
[0263] Content of 4-pentenoic acid unit 0.5 mol%
[0264] Weight average molecular weight 930000
[0265] Melting point 148℃
[0266] Storage modulus at 30°C 450MPa
[0267] Storage modulus at 60°C: 190MPa
[0268] (A-3): Fluorinated copolymer containing VdF units and HFP units
[0269] VdF / HFP=95 / 5 (mol%)
[0270] Weight average molecular weight 700000
[0271] Melting point 135℃
[0272] Storage modulus at 30°C: 320MPa
[0273] Storage modulus at 60°C: 155MPa
[0274] (A-4): Fluorinated copolymer containing VdF units, PMVE units and acrylic acid units
[0275] VdF / PMVE / acrylic acid=97.1 / 1.9 / 1.0 (mol%)
[0276] Weight average molecular weight 1070000
[0277] Melting point 147℃
[0278] <PVdF(B)>
[0279] (B-1): VdF homopolymer
[0280] Weight average molecular weight 780000
[0281] Melting point 162℃
[0282] (B-2): PVdF containing acrylic acid units
[0283] Content of acrylic acid unit: 1.0 mol%
[0284] Weight average molecular weight 1100000
[0285] Melting point 161℃
[0286] (B-3): VdF homopolymer
[0287] Weight average molecular weight 1820000
[0288] Melting point 167℃
[0289] In addition, in the examples and comparative examples, the following positive electrode active materials were used.
[0290] NMC811:LiNi 0.8 Mn 0.1 Co 0.1 O2
[0291] NCA:LiNi 0.82 Co 0.15 Al 0.03 O2
[0292] NMC622:LiNi 0.6 Mn 0.2 Co 0.2 O2
[0293] LCO:LiCoO2
[0294] In addition, in the examples and comparative examples, the following single-walled carbon nanotubes were used.
[0295] Single-walled carbon nanotube (trade name: "TUBALL BATT SWCNT", manufactured by OCSiAl)
[0296] Average outer diameter: 1.6±0.4nm
[0297] Length: 5μm or more
[0298] Average G / D ratio: 86.5±7.1
[0299] In addition, in the examples and comparative examples, the following multi-walled carbon nanotubes were used.
[0300] Average outer diameter: 11nm±4nm
[0301] Length: 5μm or more
[0302] Average G / D ratio: 1.3
[0303] Example 1
[0304] (Preparation of Composition)
[0305] In a 100-liter tank, 0.4 kg of single-layer carbon nanotubes, 98.6 kg of N-methyl-2-pyrrolidone (NMP) and 1 kg of fluorinated copolymer (A-1) were mixed using a cantilever stirrer with a rotation speed of 75 rpm and a homogenizer with an output power of 30 kW. The energy applied for homogenous mixing is 0.2 kWh per 1 kg of the mixture. The obtained mixture was treated with a high-pressure homogenizer (the mixture was passed through the homogenizer 10 times at a pressure of 700 bar). After homogenization, the suspension was taken out and filtered using a 50 μm mesh filter to prepare a 100 kg composition containing 0.4% by mass of single-layer carbon nanotubes. The optical density (absorption of luminescence at a wavelength of 500 nm caused by a composition containing 0.001% by mass of single-layer carbon nanotubes) is 0.51 absorbance units and the viscosity is 750 mPa·s, which indicates that the quality required for the composition for electrochemical devices is achieved.
[0306] (Preparation of positive electrode mixture)
[0307] After adding the obtained composition into a 1L container in a manner such that the content of single-walled carbon nanotubes is as shown in Table 1, the fluorinated copolymer (A-1) and PVdF (B-1) pre-dissolved in NMP are added and mixed respectively in a manner such that the mass ratio of the fluorinated copolymer (A) / PVdF (B) and the content of the binder are as shown in Table 1, thereby obtaining a solution. The above-obtained solution, NMC811 and acetylene black are mixed using a stirrer to obtain a mixed solution. NMP is then added to the obtained mixed solution and mixed to prepare a positive electrode mixture having a solid content concentration of 71% by mass. The composition of the obtained positive electrode mixture is shown in Table 1.
[0308] (Fabrication of positive electrode structure)
[0309] The obtained positive electrode mixture was evenly applied to one side of the positive electrode collector (aluminum foil with a thickness of 20 μm), dried at 120°C for 60 minutes to completely volatilize the NMP, and then pressed with a pressure of 10 tons using a roller press to produce a positive electrode structure. The amount of positive electrode mixture applied was 22.5 mg / cm 2 The density of the positive electrode mixture layer is 3.6 g / cm 3 .
[0310] In addition, the obtained positive electrode mixture was evenly applied to both sides of the positive electrode collector (aluminum foil with a thickness of 20 μm), dried at 120°C for 60 minutes to completely volatilize the NMP, and then pressed with a pressure of 10 tons using a roller press to produce a positive electrode structure. The coating amount of each single side of the positive electrode mixture was 28.5 mg / cm 2 The density of the positive electrode mixture layer is 3.6 g / cm 3 .
[0311] The obtained positive electrode structure was evaluated by the above method. The results are shown in Table 1.
[0312] (Production of negative electrode)
[0313] Artificial graphite powder as a negative electrode active material, an aqueous emulsion of sodium carboxymethylcellulose as a thickener (the concentration of sodium carboxymethylcellulose is 1% by mass), and an aqueous dispersion of styrene-butadiene rubber as a binder (the concentration of styrene-butadiene rubber is 50% by mass) are mixed in an aqueous solvent according to a solid content ratio of 97.6 / 1.2 / 1.2 (mass %) of the active material, the thickener, and the binder to prepare a slurry-like negative electrode mixture slurry. The negative electrode mixture slurry is evenly applied to a copper foil with a thickness of 20 μm, and after drying, it is compression-molded by a press to form a negative electrode.
[0314] (Manufacturing of lithium-ion secondary batteries)
[0315] The positive electrode (positive electrode structure), negative electrode, and polyethylene separator produced as described above were stacked in the order of negative electrode, separator, and positive electrode to produce a battery element.
[0316] The positive and negative terminals were prominently provided, and the battery element was inserted into a bag made of a double-sided laminated film with an aluminum sheet (thickness 40 μm) coated with a resin layer. Then, 1.2 g of an electrolyte (formed by dissolving LiPF6 at a concentration of 1 mol / L in a solvent of ethylene carbonate and ethyl methyl carbonate mixed at a volume ratio of 3 / 7) was injected into the bag, and vacuum-sealed to produce a sheet-shaped lithium-ion secondary battery.
[0317] <Output Characteristics>
[0318] For the lithium-ion secondary battery produced as described above, after charging to 4.2V at a constant current-constant voltage charge (hereinafter referred to as CC / CV charging) (0.1C cutoff) equivalent to 0.2C at 25°C, it is discharged to 3V at a constant current of 0.2C. This is regarded as one cycle, and the initial discharge capacity is calculated from the discharge capacity of the third cycle. Here, 1.0C represents the current value of discharging the base capacity of the battery in 1 hour, for example, 0.2C represents 1 / 5 of its current value. After the evaluation of the initial discharge capacity is completed, the battery is charged at a constant current of 0.2C at 25°C, and then discharged to 3V at a constant current of 5.0C. The ratio of the discharge capacity at 5.0C to the initial discharge capacity is calculated, and this is taken as the discharge capacity ratio (%) at 5.0C.
[0319] (5.0C discharge capacity) ÷ (0.2C initial discharge capacity) × 100 = 5.0C discharge capacity ratio (%)
[0320] Tables 1 and 3 show the results of calculations in which the value of Comparative Example 1 was set to 1.
[0321] <Cyclic Characteristics>
[0322] For the lithium ion secondary battery prepared above, after charging to 4.2V at a current CC / CV equivalent to 1.0C at 25°C (0.1C cut-off), it was discharged to 3V at a constant current of 1.0C, which was regarded as one cycle, and the initial discharge capacity was calculated from the discharge capacity. The cycle was repeated again, and the discharge capacity after 300 cycles was measured. The ratio of the discharge capacity after 300 cycles to the initial discharge capacity was calculated as the capacity retention rate (%).
[0323] (Discharge capacity after 300 cycles) ÷ (initial discharge capacity at 1.0C) × 100 = capacity retention rate (%)
[0324] Tables 1 and 3 show the results of calculations in which the value of Comparative Example 1 was set to 1.
[0325] <60℃ Storage Characteristics>
[0326] After the evaluation of the initial discharge capacity, the battery was again charged by CC / CV (0.1C cut-off) to 4.2V, and then stored at 60°C for 7 days. Then, it was discharged at 0.2C to 3V at 25°C, and the residual capacity after high-temperature storage was measured. The ratio of the residual capacity to the initial discharge capacity was calculated as the storage capacity retention rate (%).
[0327] (Remaining capacity) ÷ (initial discharge capacity) × 100 = storage capacity maintenance rate (%)
[0328] Tables 1 and 3 show the results of calculations in which the value of Comparative Example 1 was set to 1.
[0329] Embodiments 2 to 11
[0330] The positive electrode mixture was prepared in the same manner as in Example 1 except that the types of the fluorinated copolymer (A) and PVdF (B), the composition of the binder, the composition of the positive electrode mixture, etc. were changed as described in Table 1. Using the obtained positive electrode mixture, the positive electrode mixture was applied in the same coating amount as in Example 1 to prepare a positive electrode structure having a positive electrode mixture layer of the same density, and the evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.
[0331] Comparative Example 1
[0332] (Preparation of positive electrode mixture)
[0333] The fluorinated copolymer (A-1) and PVdF (B-1) were dissolved in N-methyl-2-pyrrolidone (NMP) to prepare a solution containing a binder in the mass ratio (fluorinated copolymer (A-1) / PVdF (B-1)) described in Table 1. The obtained solution, NMC811 and acetylene black were mixed with a stirrer to obtain a mixed solution. NMP was then added to the obtained mixed solution and mixed to prepare a positive electrode mixture having a solid content concentration of 71% by mass. The composition of the obtained positive electrode mixture is shown in Table 1.
[0334] (Fabrication of positive electrode structure)
[0335] A positive electrode structure was prepared in the same manner as in Example 1 except that the positive electrode mixture obtained above was used, and evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.
[0336] Comparative Example 2
[0337] A positive electrode mixture was prepared in the same manner as in Comparative Example 1 except that only PVdF (B-1) was used instead of the fluorinated copolymer (A-1) and PVdF (B-1), and a positive electrode structure was produced, which was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0338]
[0339] As shown in the results of each embodiment shown in Table 1, it can be seen that by using single-walled carbon nanotubes and a specific binder, a positive electrode structure can be obtained that maintains sufficient adhesion between the positive electrode mixture layer and the collector, while showing sufficiently low coating resistance, excellent flexibility, and is unlikely to rebound.
[0340] For example, in Example 2, a relatively small amount of single-layer carbon nanotubes is used, but by using the single-layer carbon nanotubes together with a specific binder, it is possible to achieve a balance between the close adhesion between the positive electrode mixture layer and the collector and the softness of the positive electrode structure while obtaining a sufficiently low coating resistance, and to fully suppress the rebound of the positive electrode mixture layer.
[0341] In addition, in Example 6, although the amount of binder used is less than that in Comparative Example 2, by using single-layer carbon nanotubes together with a specific binder, it is possible to achieve a balance between the close adhesion between the positive electrode mixture layer and the collector and the softness of the positive electrode structure while obtaining a sufficiently low coating resistance, and to fully suppress the rebound of the positive electrode mixture layer.
[0342] On the other hand, as shown in the results of Comparative Example 2, when single-walled carbon nanotubes and a specific binder are not used, the obtained positive electrode structure has high coating resistance, poor flexibility, and large springback even if the positive electrode mixture layer and the current collector are sufficiently adhered.
[0343] Furthermore, as shown in the results of each example shown in Table 1, it is found that the lithium ion secondary battery having a positive electrode structure obtained using a composition containing single-walled carbon nanotubes and a specific binder is excellent in all aspects of output characteristics, cycle characteristics, and 60° C. storage characteristics.
[0344] In addition, as shown in the results of Comparative Example 1, even when a specific binder is used, when single-walled carbon nanotubes are not used, not only is the coating resistance high, but also the adhesion between the positive electrode mixture layer and the collector and the softness of the positive electrode structure cannot be taken into account, and the resulting positive electrode structure has a large rebound. In addition, the lithium-ion secondary battery with such a positive electrode structure does not show sufficient output characteristics, cycle characteristics, and 60°C storage characteristics.
[0345] Example 12
[0346] After adding the composition prepared in Example 1 (composition containing 0.4% by mass of single-walled carbon nanotubes) into a 1L container in such a manner that the content of single-walled carbon nanotubes is as shown in Table 2, the fluorinated copolymer (A-1) and PVdF (B-1) pre-dissolved in NMP are added and mixed respectively in such a manner that the mass ratio of the fluorinated copolymer (A) / PVdF (B) and the content of the binder are as shown in Table 2, thereby obtaining a solution. The above-obtained solution, NCA and acetylene black are mixed using a stirrer to obtain a mixed solution. NMP is then added to the obtained mixed solution and mixed to prepare a positive electrode mixture having a solid content concentration of 71% by mass. The composition of the obtained positive electrode mixture is shown in Table 2. The stability of the obtained positive electrode mixture was evaluated by the above method. The results are shown in Table 2.
[0347] Example 13
[0348] The positive electrode mixture was prepared in the same manner as in Example 12 except that the types of the fluorinated copolymer (A) and PVdF (B), the composition of the positive electrode mixture, etc., were changed as described in Table 2 using the composition prepared in Example 4 (composition containing 0.4% by mass of single-walled carbon nanotubes). The composition of the obtained positive electrode mixture is shown in Table 2. The stability of the obtained positive electrode mixture was evaluated by the above method. The results are shown in Table 2.
[0349] Comparative Example 3
[0350] A positive electrode mixture was prepared in the same manner as in Comparative Example 2 except that the positive electrode active material was changed to NCA. The composition of the obtained positive electrode mixture is shown in Table 2. The stability of the obtained positive electrode mixture was evaluated by the above method. The results are shown in Table 2.
[0351] [Table 2]
[0352]
[0353] Examples 14 to 21
[0354] The positive electrode mixture was prepared in the same manner as in Example 1 except that the types of the fluorinated copolymer (A) and PVdF (B), the type of the positive electrode active material, the composition of the binder, the composition of the positive electrode mixture, the viscosity, etc. were changed as described in Table 3. Using the obtained positive electrode mixture, the positive electrode mixture was applied in the same coating amount as in Example 1 to prepare a positive electrode structure having a positive electrode mixture layer of the same density, and the evaluation was performed in the same manner as in Example 1. The results are shown in Table 3.
[0355] Comparative Examples 4 to 7
[0356] A positive electrode mixture was prepared in the same manner as in Comparative Example 1, except that the type of positive electrode active material, the composition of the binder, the composition of the positive electrode mixture, the viscosity, etc. were changed as shown in Table 3, and a positive electrode structure was produced and evaluated in the same manner as in Example 1. The results are shown in Table 3.
[0357]
[0358] As shown in the results of each embodiment shown in Table 3, it can be seen that even if the type of positive electrode active material is changed, sufficient adhesion between the positive electrode mixture layer and the collector can be maintained, and a positive electrode structure having sufficiently low coating resistance, excellent flexibility, and difficulty in rebounding can be obtained. In addition, it can be seen that the lithium ion secondary battery having the obtained positive electrode structure is excellent in all aspects of output characteristics, cycle characteristics, and 60°C storage characteristics.
[0359] In addition, as shown in the results of each embodiment shown in Table 1 and Table 3, by using single-walled carbon nanotubes and a specific binder, the desired effect can be fully obtained even when the amount of single-walled carbon nanotubes is small. In contrast, when multi-walled carbon nanotubes are used, sufficient adhesion and sufficiently low coating resistance cannot be obtained, and the lithium ion secondary battery having the obtained positive electrode structure does not show sufficient output characteristics, cycle characteristics, and 60°C storage characteristics (Comparative Example 6). In addition, even if the content of multi-walled carbon nanotubes is increased, sufficiently low coating resistance is not obtained, and a lithium ion secondary battery showing sufficient output characteristics is not obtained (Comparative Example 7).
Claims
1. A composition for an electrochemical device, comprising a single-walled carbon nanotube, a binder and a solvent, wherein: The composition for electrochemical devices does not contain a positive electrode active material, the binder contains a fluorinated copolymer comprising a vinylidene fluoride unit and a fluorinated monomer unit, wherein the fluorinated monomer unit does not include a vinylidene fluoride unit, the fluorinated monomer unit is at least one selected from the group consisting of a tetrafluoroethylene unit and a hexafluoropropylene unit, the content of the vinylidene fluoride unit in the fluorinated copolymer is 50.0 mol% or more relative to all monomer units, the content of the fluorinated monomer unit in the fluorinated copolymer is 1.0 mol% or more relative to all monomer units, and the solvent is at least one selected from the group consisting of N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone and β-alkoxypropionamide.
2. The composition for an electrochemical device according to claim 1, wherein The average outer diameter of the single-walled carbon nanotube is less than 2.5 nm.
3. The composition for an electrochemical device according to claim 1 or 2, wherein The average G / D ratio of the single-walled carbon nanotubes is 2 or more.
4. The composition for an electrochemical device according to claim 1 or 2, wherein The fluorinated copolymer has a storage modulus E' at 30° C. of 100 MPa to 1200 MPa obtained by dynamic viscoelasticity measurement, and a storage modulus E' at 60° C. of 50 MPa to 600 MPa.
5. The composition for an electrochemical device according to claim 1 or 2, wherein The binder further contains polyvinylidene fluoride. The composition for an electrochemical device according to claim 1 or 2, which is used to form an electrode or a separator of an electrochemical device.
7. A positive electrode mixture comprising the composition for an electrochemical device according to any one of claims 1 to 6 and a positive electrode active material, The positive electrode active material is of the general formula (1): Li y Ni 1-x M x Lithium-nickel composite oxide represented by O2, In the formula, x satisfies 0.01≤x≤0.5, y satisfies 0.9≤y≤1.2, and M represents a metal atom, which does not include Ni.
8. The positive electrode mixture according to claim 7, wherein The content of the single-walled carbon nanotubes in the positive electrode mixture is 0.001 parts by mass to 10 parts by mass based on 100 parts by mass of the positive electrode active material.
9. The positive electrode mixture according to claim 7 or 8, wherein The content of the binder in the positive electrode mixture is 0.1 parts by mass to 5.0 parts by mass based on 100 parts by mass of the positive electrode active material. 10 . A positive electrode structure comprising a current collector and a positive electrode mixture layer provided on one or both surfaces of the current collector and formed of the positive electrode mixture according to claim 7 or 8. 11 . A secondary battery comprising the positive electrode structure according to claim 10 .
Citation Information
Patent Citations
Metal foil with conductive layer and method for manufacturing same
EP3147919A1
Secondary battery, battery pack, electric vehicle, electric tool and electronic device
WO2018146865A1
Positive electrode mixture, positive electrode, and nonaqueous electrolyte secondary battery
CN102576862A
Coating liquid, coating film, and composite material
CN106795388A
Conductive agent for lithium ion secondary battery positive electrode and lithium ion secondary battery using the same
JP2012221672A